Overview of operation and experiments in the ADITYA-U tokamak. (5th June 2019) - Tanna, R.L.; Raj, Harshita; Ghosh, J.; Kumar, Rohit; Aich, Suman; Macwan, Tanmay; Kumawat, D.; Jadeja, K.A.; Patel, K.M.; Kalal, M.B.; Varia, D.S.; Sadharakiya, D.H.; et al.
Abstract: The first Indian tokamak, ADITYA, operated for over two decades with a circular poloidal limiter, has been upgraded to a tokamak named ADITYA Upgrade (ADITYA-U) to attain shaped-plasma operations with an open divertor in single and double-null configurations. Experimental research using ADITYA-U has made significant progress since the last FEC in 2016. After installation of a plasma facing component and standard tokamak diagnostics in ADITYA-U, the Phase-I plasma operations were initiated in December 2016 with a graphite toroidal belt limiter. Ohmically heated circular plasmas supported by filament pre-ionization with plasma parameters I p 80–95 kA, duration 80–180 ms, with a maximum toroidal field 1 T and chord averaged electron density 2.5 × 10 19 m −3, have been obtained. The runaway electron (RE) generation, transport and mitigation experiments, along with magneto hydrodynamic (MHD) activities and density enhancement with H2 gas puffing experiments were carried out in Phase-I, which was completed in March 2017. Preparation for the Phase-II operation in ADITYA-U includes calibration of magnetic diagnostics followed by commissioning of major diagnostics and installation of a baking system. After repeated cycles of baking the vacuum vessel up to 135 °C, the Phase-II operations resumed in February 2018 and are continuing to achieve plasma parameters close to the design parameters of circular limiter plasmas, using real-time plasma position control. The plasma current has been raised to 135 kA in Phase-II, with a maximum chord averaged electron density of 4 × 10 19 m −3 . Hydrogen gas breakdown has been observed in more than 2000 discharges, including Phase-I and Phase-II operations, without a single failure. Several experiments have been carried out, including the control of REs with the fuelling of supersonic molecular beam injection as well as sonic H2 gas puffing during current flat-top, MHD mode studies using multiple periodic gas puffs, and radiative improved modes using neon gas puffs. The experimental results from Phase-I and Phase-II operations of the ADITYA-U tokamak are discussed in this paper.